2009
DOI: 10.1002/prca.200800192
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and functional characterization of the outer membrane vesicles from the gastric pathogen Helicobacter pylori

Abstract: The gastric pathogen Helicobacter pylori causes a spectrum of gastro-duodenal diseases, which may be mediated in part by the outer membrane vesicles (OMVs) constitutively shed by the pathogen. We aimed to determine the proteome of H. pylori OMV to help evaluate the mechanisms whereby these structures confer their known immuno-modulatory and cytotoxic activities to host cells, as such disease-associated activities are also conferred by the bacterium from which the vesicles are derived. We also evaluated the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
86
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(100 citation statements)
references
References 106 publications
(123 reference statements)
5
86
0
9
Order By: Relevance
“…It has been hypothesized that the intra-inclusion luminal vesicles may represent outer membrane vesicles (OMVs) Giles et al, 2006). In other Gram-negative bacterial systems, the OMVs can engulf periplasmic and outer-membrane proteins and transport them out of bacterial organisms (Balsalobre et al, 2006;Ellis & Kuehn, 2010;Galka et al, 2008;Kim et al, 2008;Kouokam et al, 2006;Kuehn & Kesty, 2005;Mullaney et al, 2009). To be vesicalized by OMVs, CT622 and CT621 must be first translocated into the chlamydial periplasmic region or outer membrane.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that the intra-inclusion luminal vesicles may represent outer membrane vesicles (OMVs) Giles et al, 2006). In other Gram-negative bacterial systems, the OMVs can engulf periplasmic and outer-membrane proteins and transport them out of bacterial organisms (Balsalobre et al, 2006;Ellis & Kuehn, 2010;Galka et al, 2008;Kim et al, 2008;Kouokam et al, 2006;Kuehn & Kesty, 2005;Mullaney et al, 2009). To be vesicalized by OMVs, CT622 and CT621 must be first translocated into the chlamydial periplasmic region or outer membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The assertion that Hp-Tpx is involved in defense against exogenous oxidative attack is strengthened by the fact that Hp-Tpx has been reported as a potential membrane-associated protein (4, 108) and has been detected in H. pylori outer membrane vesicles (68). Although other studies have failed to detect Hp-Tpx extracellularly (89), this may reflect differences in growth conditions, as Tpx has been shown to have variable extracellular expression in other bacterial pathogens, depending on media composition and atmospheric oxygen concentration (38).…”
mentioning
confidence: 99%
“…Our own immunogold electron-microscopic analysis found that cell surface Hp-SOD is heavily expressed on the flagella of H. pylori and that Hp-SOD is also present in secreted outer membrane vesicles (Fig. 2) (68). While the role of these outer membrane vesicles in the pathophysiology of H. pylori is incompletely understood, they are thought to represent extracellular release of bioactive compounds for interbacterial and host interactions and are known to be capable of binding to host epithelial cells (77).…”
mentioning
confidence: 99%
“…In addition to free soluble secretion, both VacA and GGT are packaged into MV (31,47) by H. pylori. MV are more likely to cross the epithelial barrier than whole bacteria and so might exert long-range effects on host immune cells.…”
Section: Discussionmentioning
confidence: 99%